Dengue prevention and control method for aedes mosquitoes breeding in Selangor, Malaysia - Krishnamurthy, Pavinar (2021)
Dengue fever is one of the most dangerous arthropod-borne viral diseases in Malaysia, with a high mortality rate. In Malaysia, dengue breeding has become a serious public health issue. However, the potential to prevent the dengue epidemic must begin at the outset. There are some formalities on most issues in Malaysia, the influences tropical and subtropical in Selangor, Malaysia transcendently in urban and semi-urban territories. Dengue infections are spread to humans through the bites of a striped Aedes aegypti mosquito that has recently nibbled a contaminated individual. Dengue fever does not spread from person to person. It is only transmitted through the bite of a tainted mosquito. The primary research problem begins with a massive issue in the dengue epidemic, which is increasing in Selangor, Malaysia, and necessitates specific prevention techniques, particularly in improving the product to prevent the dengue epidemic. Furthermore, the main study is about Aedes mosquitoes spreading quickly due to reclaimed water in the housing area, playground, and many more. This provides ideal breeding conditions for Aedes mosquitoes. The goal of this study is to identify a method for preventing the dengue epidemic in specific dengue breeding areas, such as Selangor, Malaysia, as a result of a contaminated Aedes mosquito bite. A specific relevant design of an existing product must be improved in order to combat Aedes mosquitoes with a proper technique and method to destroy Aedes breeding places with the fogging function. This research would then help to reduce the number of dengue cases. Therefore, the study of design in a competency framework for a portable fogging machine is required to come up with a proper design proposal in the fogging machine that can be improved according to the most relevant techniques and methods to reduce the cases that are becoming critical in Selangor Malaysia.